Implementación de un programa de orientación vocacional para los estudiantes del octavo año de educación general básica “A” y “B” de los talleres escuela San Patricio durante el periodo de marzo- julio del 2016 - Zapata Villagómez, Katherine Mercedes (2017)
The importance of vocational guidance in young people is to develop their capacities so that they can make decisions in a responsible and freeway both now and for the rest of their lives. Therefore, the main objective of the present work is to analyze the effectiveness of the implementation of a Vocational Guidance program for the eighth grade students of Basic General Education "A" and "B" of the San Patricio School Workshops through the systematization of the Psych pedagogical process. Methodologically, the following tests were applied: (Vocational interests, cognitive abilities and characterological traits), along with the use of attendance records, workshop micro projects, initial surveys and vocational data sheets. This allows students to build their life plan with the guidance counselor who coordinates and guides students for decision making.